Epidemiology of oral mucosal lesions in Slovenia - Kansky, Andrej (Radiology and oncology (Ljubljana), 2018)
Background Among the diseases of oral mucosa, malignant tumors are the most dangerous, but not the most common lesions that might appear in the oral cavity. Since most of the studies are focused on the detection of cancer in the oral cavity, we were interested in detecting the frequency of benign changes of the oral mucosa in Slovene population. Oral mucosal lesions are important pointer of oral health and quality of life, especially in elderly. The prevalence of oral mucosal lesions, together with information on the risk habits associated with oral health, such as tobacco and alcohol use, can help in planning future oral health studies and screening programs. Patients and methods Survey upon oral mucosal lesions was conducted during the national project for oral cancer screening in spring 2017 in the Slovenia in which more than 50% of dentists participated and 2395 patients (904 men and 1491 women) were included. Results Clinical examination, which was conducted according to the WHO standards revealed that 645 patients (27%) had oral mucosal lesions. The ten most common oral lesions detected were fibroma, gingivitis, Fordyce spots, white coated tongue, cheek biting, linea alba, denture stomatitis, geographic tongue, recurrent aphthous ulcerations and lichen planus. Conclusions Overall, these epidemiological data suggest need for specific health policies for prevention, diagnosis and treatment of oral mucosal lesions.
Keywords: epidemiološki podatki; maligni tumorji; ustna sluznica; ustne lezije